Permanent implants for lip augmentation: Results from a retrospective study and presentation of tips and tricks. Issue 5 (May 2017) - Guida, S.; Mandel, V.D.; Farnetani, F.; Manola, C.M.; Rubino, G.; Ruzzu, S.; Pellacani, G.; Longo, C.; Urtis, G.G.
Summary: Background: Requests for lip augmentation are increasing because of expanding media exposure and consumer needs. Temporary effects can be obtained by several techniques, but a recent procedure consisting of lip prosthesis implantation, offering a permanent result, is emerging. Accordingly, the implantation of solid lip prosthesis represents an innovation in the field of esthetic medicine and surgery. Methods: A total of 100 women with atrophic or hypoplastic lips were treated with lip implants. The treatment was performed in a single session, and controls were scheduled at fixed time intervals. A standard digital photo was used for measurement and analysis. Data concerning patient satisfaction and complications of the technique were collected and analyzed. Variations to the original technique were also discussed. Results: Patient evaluation revealed that a permanent and natural result without discomfort for the patient and/or the partner was reached with the implantation of silicone prosthesis in the upper and/or lower lip. Swelling, bruising, and malpositions were the most frequent adverse events. A case of severe edema was reported. Practical tricks acquired through experience were discussed to prevent complications. Conclusions: One of the most widespreading methods for lip remodeling is hyaluronic acid injections. Nevertheless, hyaluronic acid has a variable duration, and it is not always the first choice. This context allowed for the development of other techniques such as the implantation of silicone prosthesis. The advantages of this prosthesis are as follows: safety, definitive result, and reversibility considering the possibility to remove the implanted prosthesis in the case of a request.